Pain modulation by nitric oxide in the spinal cord. - Freire, Marco Aurelio M.; Guimarães, Joanilson S.; Gomes-Leal, Walace; Pereira, Antonio (Frontiers in Neuroscience, 2009)
Nitric oxide (NO) is a versatile messenger molecule first associated with endothelial relaxing effects. In the central nervous system (CNS), NO synthesis is primarily triggered by activation of N-methyl-D-aspartate (NMDA) receptors and has a Janus face, with both beneficial and harmful properties, depending on concentration and the identity of its synthetic enzyme isoform. There are three isoforms of the NO synthesizing enzyme nitric oxide synthase (NOS): neuronal (nNOS), endothelial (eNOS), and inducible nitric oxide synthase (iNOS), each one involved with specific events in the brain. In CNS, nNOS is involved with modulation of synaptic transmission through long-term potentiation in several regions, including nociceptive circuits in the spinal cord. Here, we review the role played by NO on central pain sensitization.